Multiple cues in social perception: The time course of processing race and facial expression. - Kubota, Jennifer T.; Ito, Tiffany A. (Journal of Experimental Social Psychology, 2007)
The purpose of the present study was to examine the time course of race and expression processing to determine how these cues influence early perceptual as well as explicit categorization judgments. Despite their importance in social perception, little research has examined how social category information and emotional expression are processed over time. Moreover, although models of face processing suggest that the two cues should be processed independently, this has rarely been directly examined. Event-related brain potentials were recorded as participants made race and emotion categorization judgments of Black and White men posing either happy, angry, or neutral expressions. Our findings support that processing of race and emotion cues occur independently and in parallel, relatively early in processing. Copyright (c) 2007 Elsevier Inc.